2021
DOI: 10.1007/s40615-021-01168-4
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Lead to Racial Disparities in Outcomes After Total Knee Arthroplasty?

Abstract: Total knee arthroplasty (TKA) is one of the most commonly performed, major elective surgeries in the USA. African American TKA patients on average experience worse clinical outcomes than whites, including lower improvements in patient-reported outcomes and higher rates of complications, hospital readmissions, and reoperations. The mechanisms leading to these racial health disparities are unclear, but likely involve patient, provider, healthcare system, and societal factors. Lower physical and mental health at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…30 Issues of health disparity are multifaceted; and individual, health care, and societal factors may all contribute to worse outcomes in Black patients. 32 Early adverse events were associated with worse PROMIS 10 MH scores at 1 year postoperatively, which demonstrates that physical setbacks early in rehabilitation can have lasting mental effects in patients. Further work exploring and calculating MIDs within subgroups of patients that may differ could improve the delivery and interpretation of treatments for all patients.…”
Section: Discussionmentioning
confidence: 92%
“…30 Issues of health disparity are multifaceted; and individual, health care, and societal factors may all contribute to worse outcomes in Black patients. 32 Early adverse events were associated with worse PROMIS 10 MH scores at 1 year postoperatively, which demonstrates that physical setbacks early in rehabilitation can have lasting mental effects in patients. Further work exploring and calculating MIDs within subgroups of patients that may differ could improve the delivery and interpretation of treatments for all patients.…”
Section: Discussionmentioning
confidence: 92%
“…Prior studies in various medical and surgical subspecialties have analyzed the relationships among race, ethnicity, and sociodemographic factors in the context of health outcomes 1,21,[37][38][39][40][41][42] . Findings regarding which factors predominantly affect score variation have differed throughout the orthopaedic literature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on understanding social determinants of health that influence PROM scores, both in response to treatment 8,14-16,18 and at initial presentation 17,19-23 . Prior studies investigating baseline PROMs across U.S. orthopaedic populations found that Black, Hispanic, non-English-speaking, less-educated, and lower-income patients had worse outcomes 15,24-27 .…”
mentioning
confidence: 99%
“…Leadership in orthopaedics at the national and regional level remains deficient in terms of Black faces [3]. Black patients continue to experience unnecessary and preventable complications, poorer access to care, and discrimination when they do encounter a provider [1,4].…”
mentioning
confidence: 99%